Jordan - Development Policy Review : A Reforming State in a Volatile Region - World Bank (Washington, DC, 2013)
Since the early 1990s, Jordan has initiated efforts toward far-reaching stabilization and structural reform. The reforms have aimed at laying the foundations for a reduced role of the state, private-sector-export-oriented-growth, employment, poverty reduction, and overall improvement in the welfare of the population. Due to this intensive effort, inflation has been reduced, the current account of the balance of payments has been stabilized, and budget deficits have been reduced. In addition, structural reforms have encompassed domestic taxation/subsidy policies, trade liberalization policies, monetary/financial sector policies, exchange rate policies, administered prices, and privatization. The reforms initiated since 1989 have made Jordan one of the leaders of reform in the Middle East and north Africa region, despite its experiencing several changes in government and adverse external shocks in the 1990s. The country has further integrated into the global economy, with a major shift in trade policy that included an Association Agreement with the European Union in 1999, membership in the World Trade Organization in 2000, and a free-trade agreement with the USA in 2001. Jordan has achieved progress in privatization, most notably in public utilities. Despite deep structural reforms and macroeconomic stability, strong and sustainable growth in real output has been elusive. Three factors have been identified as major constraints to faster growth: 1) external volatility and adverse regional neighborhood effects; 2) slow response of private investment, both in its level and in terms of productivity; and 3) significant export competitiveness problems. Increasing growth performance as a means to reduce poverty and improve the welfare of Jordanians is the first key development challenge identified in this Development Policy Review. The other key development challenge in Jordan is to improve the quality and efficiency of its core public services. Efficient delivery of public services is especially critical in education and health and in the water sectors.